2011
DOI: 10.2478/v10172-011-0099-4
|View full text |Cite
|
Sign up to set email alerts
|

Cu Thin Films Deposited by DC Magnetron Sputtering for Contact Surfaces on Electronic Components

Abstract: The results of the DC magnetron sputtering of copper thin films with different parameters of deposition are presented. The main aim of studies was to determine the influence of current value, time of deposition and target-substrate distance on morphology and grain size of obtained copper thin films. The effects of film's thickness on the resistivity of copper thin films were investigated. The influence of parameters on the rate of deposition was also determined. The possibility of application of resulting film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…Similar observations were already noticed in literature on films prepared from SFCD with alcohols or hydrogen as reducing agent [22], sputtered [5,18,23,24], metal vapor vacuum arc, ion implantation and ion beam assistant deposition technologies [25], aerosol deposition [8], pulse electroplating [26], electrodeposited [27] and CVD [28] on various substrates. An increase of the I(111)/I(200) ratio (value equal to 2.17 if intensities are taken from ICDD 01-085-1326 standard data) and values superior to 0.33 are noticed when the substrate temperature increases or after annealing for SCFD films.…”
Section: Texture Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…Similar observations were already noticed in literature on films prepared from SFCD with alcohols or hydrogen as reducing agent [22], sputtered [5,18,23,24], metal vapor vacuum arc, ion implantation and ion beam assistant deposition technologies [25], aerosol deposition [8], pulse electroplating [26], electrodeposited [27] and CVD [28] on various substrates. An increase of the I(111)/I(200) ratio (value equal to 2.17 if intensities are taken from ICDD 01-085-1326 standard data) and values superior to 0.33 are noticed when the substrate temperature increases or after annealing for SCFD films.…”
Section: Texture Propertiessupporting
confidence: 86%
“…Mech et al [23] investigated the effect of DC magnetron sputtered copper film's thickness on the resistivity of thin films. Conducted studies showed that the bulk resistivity for films thicker than 250 nm were constant (1.87 μΩ·cm) even if grain size increased with sputtering time.…”
Section: Surface Morphology and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were carried out in the closed Teflon R cell with three electrodes. The working electrode were slide glass covered of 300 nm thick gold film with the area of 0.38 cm 2 deposited by magnetron sputtering described in our previous paper [29]. A platinum spring was used as a counter electrode and an Ag/AgCl leakless electrode as a reference electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The working electrode was freshly evaporated copper on glass by magnetron sputtering technique [20]. Deposition began with a 10 nm adhesion layer of Ti, followed by 300 nm of Cu deposition.…”
Section: Methodsmentioning
confidence: 99%